The Mekong delta system : - Renauld, Fabrice G. (Springer, 2012)
This book about the Mekong Delta presents a unique collection of state-of-the-art contributions by international experts from different scientific disciplines about the characteristics and pressing water-related challenges of the Mekong Delta in Vietnam. The Mekong Delta belongs to one of the areas, which are to expect the largest challenges concerning environmental change and climate change induced sea level rise .